Pengaruh Wadah dan Lama Penyimpanan Terhadap Viabilitas dan Vigor Benih Hotong (Setaria italica (L) Beauv) - Sinurat, Liberty; Riry, Johan; Makaruku, Marlita H (Universitas Pattimura, 2023)
The aim of this research is that hotong seeds can be preserved for a long time so that they can be stored and used for cultivation in the next planting season. This research was conducted at the Tissue Culture Laboratory and Plant Physiology Laboratory at the Faculty of Agriculture, Pattimura University, Ambon, which took place from February to May 2021. Completely randomized design method, two factors, three replications. The first factor was seeds in open space (A0), seeds in aluminum foil (A1), seeds in glass bottles (A2), seeds in clear plastic (A3), and seeds in white cloth (A4). Another factor is the retention time (B) which consists of three stages, namely: 1 month (B1), 2 months (B2), and 3 months (B3) storage. BNJ test and Anova analysis at 95% confidence level. The treatment to maintain the quality of the hotong seeds was the 3rd month storage aluminum foil (A3B3) which could maintain a moisture content of 9.4%, PTM 80.67%, and the growth rate and vigor of hotong seeds at 81%, and the worst treatment in maintaining the quality of viability and vigor. seeds were calico fabric treated in the 3rd month of storage (A1B3).